2023
DOI: 10.1038/s41598-023-31118-5
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Strongyloides stercoralis infection increases presence of the Ruminococcus torques group in the gut and alters the microbial proteome

Abstract: We explored the impact of chronic Strongyloides stercoralis infection on the gut microbiome and microbial activity in a longitudinal study. At baseline (time-point T0), 42 fecal samples from matched individuals (21 positive for strongyloidiasis and 21 negative) were subjected to microbiome 16S-rRNA sequencing. Those positive at T0 (untreated then because of COVID19 lockdowns) were retested one year later (T1). Persistent infection in these individuals indicated chronic strongyloidiasis: they were treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
(51 reference statements)
0
4
1
Order By: Relevance
“…27 Anaerofilum is markedly associated with inflammatory agents related to increased lipid metabolic disorders. 28 However, previous findings revealed a potential beneficial role of Anaerostipes and Fusicatenibacter, 29 but our research demonstrated the opposite results. These bacteria cited above are closely related to pro-inflammatory cytokines and specific lipid metabolisms, which can promote the expression of serum inflammation in rats.…”
Section: Papercontrasting
confidence: 87%
“…27 Anaerofilum is markedly associated with inflammatory agents related to increased lipid metabolic disorders. 28 However, previous findings revealed a potential beneficial role of Anaerostipes and Fusicatenibacter, 29 but our research demonstrated the opposite results. These bacteria cited above are closely related to pro-inflammatory cytokines and specific lipid metabolisms, which can promote the expression of serum inflammation in rats.…”
Section: Papercontrasting
confidence: 87%
“…A recent study from the same region of Thailand also found no significant differences in gut microbiome structure and diversity between healthy individuals with or without S. stercoralis infection [ 23 ]. Recently, a longitudinal study found no significant changes in gut diversity before and after treatment of S. stercoralis infection in healthy individuals [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with prior studies ( Worby et al, 2022b ), the abundance of Ruminococcaceae decreased in patients with recurrent UTI, suggesting that Ruminococcus could serve as a potential marker for dysbiosis in recurrent cystitis ( Graziani et al, 2022 ). The f_Ruminococcaceae is also known to be significantly affected by chronic infections ( Martinez et al, 2022 ; Tran et al, 2023 ) and the administration of antibiotics ( Ross et al, 2016 ). Although direct evidence linking Ruminococcaceae UCG010 to UTI remains elusive, some studies have proposed that a higher abundance of this bacterium in the GM may correlate with decreased risks of type 2 diabetes ( Lyu et al, 2023 ), non-alcoholic fatty liver disease ( Tsai et al, 2020 ), and obesity ( Nseir et al, 2015 ), each being a risk factor for UTI.…”
Section: Discussionmentioning
confidence: 99%